2022
DOI: 10.3389/fimmu.2022.873408
|View full text |Cite
|
Sign up to set email alerts
|

Similar CD4/CD8 Ratio Recovery After Initiation of Dolutegravir Plus Lamivudine Versus Dolutegravir or Bictegravir-Based Three-Drug Regimens in Naive Adults With HIV

Abstract: BackgroundThe initiation of antiretroviral treatment based on a 2-drug regimen (2DR) with dolutegravir plus lamivudine has demonstrated non-inferior efficacy than dolutegravir-based three-drug regimens (3DR). We aimed to assess whether the treatment initiation with this 2DR has a different impact on the CD4/CD8 ratio recovery than INSTI-based 3DR.MethodsWe emulated a target trial using observational data from the Spanish HIV Research Network cohort (CoRIS). The outcomes of interest were the normalization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…As we learned from the experiences using dolutegravir in monotherapy (12,13), even under this inferior regimen, a readily measurable virological event such as a viral rebound can be slow to occur. Llibre et al ( 1) noted that we have recently reported a similar rate of CD4/CD8 ratio recovery after 48 weeks of dolutegravir plus lamivudine versus dolutegravir or bictegravir-based 3DR in naïve PLWH (14). These results are reassuring, but we could only evaluate differences after 48 weeks of ART, and as we previously showed, the CD4/CD8 ratio correlates poorly with inflammatory biomarkers (15).…”
supporting
confidence: 71%
“…As we learned from the experiences using dolutegravir in monotherapy (12,13), even under this inferior regimen, a readily measurable virological event such as a viral rebound can be slow to occur. Llibre et al ( 1) noted that we have recently reported a similar rate of CD4/CD8 ratio recovery after 48 weeks of dolutegravir plus lamivudine versus dolutegravir or bictegravir-based 3DR in naïve PLWH (14). These results are reassuring, but we could only evaluate differences after 48 weeks of ART, and as we previously showed, the CD4/CD8 ratio correlates poorly with inflammatory biomarkers (15).…”
supporting
confidence: 71%
“…Once HIV suppression has been achieved and maintained, it is highly unlikely that different dolutegravir-or bictegravir-based antiretroviral regimens could be associated with significantly different levels of inflammation or immune activation unless they include drugs with intrinsic toxicity. Actually, a similar CD4/CD8 ratio recovery has been reported after initiation of a 2DR (dolutegravir plus lamivudine) versus dolutegravir-or bictegravir-based 3DR in naive PLWH (6).…”
supporting
confidence: 68%
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy studies (35%) reported in the title that the study aimed to emulate a target trial; 180 (90%) did so in the Methods section. Twenty studies (10%) reported the study was prospectively registered, 16 of these 20 (80%)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation